Multisystem Inflammatory Syndrome Leading to Myocardial Infarction After SARS-CoV-2 Vaccination - Yuki Shimada; Masao Takigami; Shunya Kaneshita; Kenji Yanishi; Satoaki Matoba; Yutaka Kawahito (Annals of Internal Medicine: Clinical Cases)
The most common adverse effects of SARS-CoV-2 vaccines are injection site reactions and systemic symptoms, such as fever and malaise, which are typically self-limiting. Multisystem inflammatory syndrome after SARS-CoV-2 vaccination (MIS-V) is rare. In this report, we describe a case of a 22-year-old man who developed MIS-V with myocardial infarction. Optical coherence tomography (OCT) showed blurring of intravascular structure, intimal thickening, and medial vessel destruction. High-dose glucocorticoid and antithrombotic therapy were effective as shown through improvement in OCT findings.